Experimental study on a new prototype design of electric bus vehicle structure under torsion loading conditions - Budi Haryanto; Danardono Agus Sumarsono; Djoko Wahyu Karmiadji; Mohammad Adhitya; Stevanus Brian Kristianto; Lukyawan Pama Deprian (Universitas Muhammadiyah Magelang, 2025)
Vehicles commonly encounter uneven road conditions, which can lead to torsional deformation of the frame structure. The results of finite element analysis (FEA) indicate that the highest stress occurs under torsion loading conditions. To validate these simulation results, an experimental study was conducted involving static load testing under torsional loading conditions on a hybrid frame structure, composed of SS 400 carbon steel and 6061 aluminum alloy, designed for a 70-passenger electric bus. The test was performed by applying a static load of 6,825 kg as sandbags on the seating area and aisle, and supporting the frame on three wheels only. Strain measurements were recorded using 28 strain gauges: 20 on the SS 400 carbon steel underframe and 8 on the 6061 aluminum alloy structure of the side and roof frames. The total load was the weight of 70 passengers plus a 30% dynamic load factor. Experimental analysis revealed a maximum stress value of 76.42 MPa in the SS 400 carbon steel of the underframe at location 9 in the central section of the underframe. In the 6061 aluminum alloy structure, the maximum stress value of 15.56 MPa was obtained in the roof frame directly below the air conditioner unit. Overall, the measured stress values were within the elastic ranges of the materials used, demonstrating structural integrity under load. The average difference between the experimental results for stress and the finite element analysis (FEA) simulation was approximately 11.21%.